Responses to Environmental Threats in an Age of Globalization - Jennifer Clapp (Managing Leviathan: Environmental Politics and the Administrative State, 2005)
Bureaucracies, including large corporations and governmental agencies, are based on hierarchy and prone to secrecy. They encourage highly specialized forms of knowledge and structure themselves in compartmentalized ways. In stark contrast, environmental problems cut across all artificial divisions and boundaries. Managing Leviathan illustrates the nature of environmental problems from genetically modified crops to climate change, from urban sprawl to toxic chemicals to trace pharmaceuticals in our water supply. Understanding these problems, and how they might be resolved, requires that we transcend the divisions of government, economy, and knowledge. Solutions often also require the mobilization of citizen knowledge and values. Are governments and bureaucracies up to the complex task? How might they adapt to be better suited to meet the new environmental challenges that continuously arise? This extensively revised edition of Managing Leviathan expands from a North American to a global perspective and includes new articles on both European and Australian experiences as well as on transnational environmental issues. The overall pattern is remarkably clear: environmental administration demands integrative thinking and new forms of direct public involvement in governance.